Active surveillance for Aujeszky's disease and biosecurity aspects of swine farms in Espirito Santo State, Brazil - Scofano, Agostinho Sergio; Teixeira, Jessica Nogueira [UNESP]; Orlandi, Sarah Salvador; Goulart, Patricia Riddell Millar; Cunha, Nathalie Costa da; Nascimento, Elmiro Rosendo do (Univ Federal Santa Maria, 2024)
Aujeszky's Disease (AD) is a highly infectious swine disease caused by Suid herpesvirus 1 (SuHV 1). The present study evaluated the biosafety of commercial swine farms and carried out the first serological survey for Aujeszky's Disease in Espirito Santo State, Brazil. A total of 55 farms in 27 municipalities of the state were selected, where 416 swine serum samples were collected to be submitted to serological diagnosis for AD. Finally, a survey was carried out using a questionnaire to obtain information on the biosecurity of the farms. The results by the ELISA technique indicated the absence of antibodies for AD. Regarding the biosecurity of the farms, 56.4% of the farms did not meet the requirement of internal isolation, 67.3% did not have changing rooms, 72.7% did not provide specific clothing for employees and visitors, 85.5% did not require visitors bathe to access the sheds and only 10.9% of the farms controlled the flow of visitors and vehicles accessing the property. Another noteworthy factor is that only 25.5% of the farms had an area to quarantine replacement animals and 69.1% had an access ramp located close to the animal pens. With the results, it was concluded that there is a need to improve biosecurity measures on commercial farms in the state of Espirito Santo and that there was no presence of Aujeszky's Disease in the evaluated animals.
Keywords: Aujeszky; pseudorabies; swine; serology; biosecurity; surveillance